PENDAMPINGAN EVALUASI KERJA TENAGA KEPENDIDIKAN MELALUI PELATIHAN LITERASI TEKNOLOGI PERKANTORAN - Antonius Rachmat Chrismanto; Wibowo, Argo; Halim Budi Santoso; Katon Wijana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2024)
The role of staff is important in educational institutions because they help to manage administrative matters. Technological advancements, such as Microsoft Office 365, offer staff tools to streamline administrative tasks efficiently. The applications within Microsoft Office 365 are tailored to support administrative workflows, allowing staff to prioritize student learning experiences. SMA BOPKRI 1 Yogyakarta employs educators who believe that leveraging technology can balance teaching and administrative duties. In collaboration with FTI UKDW, a community service initiative was conducted to assist staff in understanding and implementing Microsoft Office 365 applications as a performance evaluation tool. This training covered four main applications: MS Word, MS PowerPoint, MS Excel, and Canva. The initiative was executed as planned despite scheduling challenges. Training sessions held during workdays and hours hindered optimal participation. Thus, conducting them during inter-semester breaks or school holidays is recommended. The training modules were tailored to the school's needs, and the implementation results showed improved administrative capabilities. The outcomes of the training can be used as a means to evaluate the information technology literacy of educational staff.